A disturbance observer based approach to current control of PMSM drives for torque ripple reduction. Issue 4 (2019) - Kim, Yong-Hun; Choi, Kyunghwan; Kim, Seok-Kyoon; Kim, Kyung-Soo
Abstract: This paper deals with the reduction of torque ripple in a PMSM (permanent magnet synchronous motor) drive using disturbance observer based control. The current ripple is periodically synchronized to the position of the rotor in the form of distorted back-EMF voltage. Therefore, the current ripple is concentrated on the rotation frequency and integral multiples in the frequency domain. In this paper, a method is introduced to reduce the current ripple while maintaining reference tracking performance without a significant change of the controller by intensively increasing the disturbance suppression performance of the frequency band corresponding to the current ripple. The proposed method is verified that a steady-state 58% ripple reduction in 500W SPMSM in the experiments.